Vanadium-tungsten bimetallic oxide electrochromic film and preparation method thereof

By preparing a multi-level vanadium-tungsten bimetallic oxide hexagonal star-shaped thin film, the shortcomings of inorganic electrochromic materials in terms of energy storage capacity and optical modulation were overcome, and efficient electrochemical reaction and stable electrochromic performance were achieved.

CN120891685AActive Publication Date: 2025-11-04SHANGHAI CENTAUR ENTERPRISE DEV GRP CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511430347.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-09
Publication Date
2025-11-04
Estimated Expiration
2045-10-09

AI Technical Summary

Technical Problem

Existing inorganic electrochromic materials, such as WO3, have limited energy storage capacity, making it difficult to achieve efficient optical modulation and electrochemical reactivity.

Method used

A one-step hydrothermal method was used to prepare hexagonal star-shaped vanadium-tungsten bimetallic oxide films with multi-level structures. By controlling the molar ratio of vanadium to tungsten in the precursor solution, the controllable synthesis of vanadium-tungsten bimetallic oxide films was achieved, enhancing the electrochemical reaction active sites and structural stability.

Benefits of technology

It improves the areal capacitance and cycling stability of the thin film while maintaining high light modulation amplitude and coloring efficiency. The process is simple, low-cost, and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120891685A_ABST
    Figure CN120891685A_ABST
Patent Text Reader

Abstract

The invention discloses a vanadium-tungsten bimetallic oxide electrochromic film and a preparation method thereof.The preparation method comprises the steps that S1, ammonium paratungstate hydrate, ammonium metavanadate and oxalic acid dihydrate are dissolved in deionized water, and a hydrothermal reaction precursor solution is obtained after stirring; and S2, carrying out hydrothermal reaction on the conductive glass to obtain the conductive glass. Controllable synthesis of the vanadium-tungsten bimetallic oxide film is realized by controlling the molar ratio of vanadium to tungsten in the precursor solution. The invention also discloses the vanadium-tungsten bimetallic oxide electrochromic film prepared by the method, and an electrochromic device comprising the film. The vanadium-tungsten oxide thin film prepared by the method has a unique nano hexagonal star-shaped structure, has a high specific surface area and excellent structural stability, not only can improve abundant electrochemical reaction active sites and remarkably improve the area capacitance of a thin film material, but also can improve the cycling stability; and meanwhile, the light modulation amplitude and the coloring efficiency are relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of electrochromic thin films, and particularly relates to a vanadium-tungsten bimetallic oxide electrochromic thin film and a preparation method thereof. BACKGROUND

[0002] Electrochromism refers to the continuous and reversible change of optical properties of some materials due to the simultaneous intercalation or deintercalation of ions and electrons under the driving of an applied voltage, which visually presents as the change of color of the materials. According to the material category, electrochromic materials can be divided into inorganic electrochromic materials and organic electrochromic materials. Inorganic electrochromic materials mainly include transition metal oxides, Prussian blue and polyoxometalates, which are widely studied due to the characteristics of rich composition, adjustable structure and outstanding electrochemical performance.

[0003] It is known that electrochromism usually pursues to achieve large optical modulation under a small amount of charge injection, thereby providing high coloration efficiency and realizing high energy-saving efficiency. Electrochemical energy storage requires a large charge density to obtain a high energy storage capacity. As the most widely studied inorganic electrochromic material at present, WO3 has excellent color-changing performance such as large optical modulation amplitude, high coloration efficiency and fast response speed, but its energy storage capacity is relatively low. For example, Zhao et al. ‎ reported a nanostructured WO3 electrode for electrochromic energy storage applications, which exhibited optical modulation amplitudes of 70.8 / 71.7% at 633 / 1200 nm, and an area capacitance of only 40.6 mAh·m -2 at a current density of 1 A·m -2 Chem. Eng. J 2024, 485,149350, Cathode / Anode electrodes for large-area bifunctional electrochemical devices prepared by a novel Na3Cit-assisted chemical deposition method). Roy et al. synthesized WO3·H2O films by a hydrothermal method, which exhibited an optical modulation amplitude of 42% at 700 nm and an area capacitance of 45 mAh·m -2 at 0.4 A·m -2 ACS Appl. Mater. Interfaces ​​2024, 16(30), 39539-39550, Electrochromic and Energy Storage Performance Enhancement by Introducing Jahn-Teller Distortion: Experimental and Theoretical Study. SUMMARY

[0004] To solve the above technical problems, the purpose of the present application is to provide a vanadium tungsten bimetallic oxide electrochromic film and a preparation method thereof, a self-assembled vanadium tungsten bimetallic oxide hexagonal star film with a multi-level structure is prepared by one-step hydrothermal method. This unique structure has the advantages of large active specific surface area and better structural stability, which not only can provide more electrochemical reaction active sites, improve the area capacitance, but also can enhance the cycle stability and maintain a high light modulation amplitude. The preparation method of the present application is simple, and the vanadium tungsten bimetallic oxide electrochromic film with high and uniform binding force can be obtained.

[0005] The purpose of the present application is realized by the following technical solutions: In a first aspect, the present application provides a preparation method of a vanadium tungsten bimetallic oxide electrochromic film, comprising the following steps: S1, dissolving ammonium paratungstate hydrate, ammonium metavanadate and oxalic acid dihydrate in deionized water, and stirring to obtain a hydrothermal reaction precursor solution; S2, carrying out hydrothermal reaction on the conductive glass, and obtaining the vanadium tungsten bimetallic oxide electrochromic film.

[0006] As some specific embodiments of the present application, in step S1, the concentration of ammonium metavanadate in the hydrothermal reaction precursor solution is 0.045-0.1 mol / L.

[0007] As some specific embodiments of the present application, in step S1, the molar ratio of vanadium element to tungsten element in the hydrothermal reaction precursor solution is 3:1-7:1.

[0008] As some specific embodiments of the present application, in step S1, the molar ratio of ammonium metavanadate to oxalic acid dihydrate in the hydrothermal reaction precursor solution is 1:2-2:1.

[0009] As some specific embodiments of the present application, in step S1, the stirring is heating stirring, and the temperature of the heating stirring is 70-90 ℃.

[0010] As some specific embodiments of the present application, in step S2, the temperature of the hydrothermal reaction is 150-180 ℃, and the time of the hydrothermal reaction is 1-4 h.

[0011] As some specific embodiments of the present application, in step S2, the conductive glass is selected from any one of FTO (fluorine-doped tin dioxide) conductive glass, ITO conductive glass, and AZO conductive glass.

[0012] As some specific embodiments of the present application, step S2 specifically comprises the following steps: S21, transferring the hydrothermal reaction precursor solution obtained in step S1 into a hydrothermal reaction kettle, and obliquely placing a piece of conductive glass into the hydrothermal reaction kettle, with the conductive surface facing downward, and sealing the hydrothermal reaction kettle; S22, placing the sealed hydrothermal reaction kettle into a constant-temperature drying box for hydrothermal reaction, and naturally cooling to room temperature after the reaction is completed; S23, taking out the conductive glass in the hydrothermal reaction kettle, and obtaining the vanadium-tungsten bimetallic oxide after cleaning and drying.

[0013] In a second aspect, the present application provides a vanadium-tungsten bimetallic oxide electrochromic film prepared by the preparation method described in any one of the above.

[0014] In a third aspect, the present application provides an electrochromic device comprising the vanadium-tungsten bimetallic oxide electrochromic film described above.

[0015] The vanadium-tungsten bimetallic oxide film prepared on the FTO conductive glass has a nanometer hexagonal star-shaped surface microstructure and good electrochromic effect.

[0016] Compared with the prior art, the present application has the following beneficial effects: 1) The present application realizes controllable synthesis of the vanadium-tungsten bimetallic oxide film by controlling the vanadium-tungsten molar ratio in the precursor solution; 2) The vanadium-tungsten oxide film prepared by the present application has a unique nanometer hexagonal star-shaped structure, has high specific surface area and excellent structural stability, can not only improve the rich electrochemical reaction active sites and significantly improve the area capacitance of the film material, but also can improve the cycle stability; 3) The preparation process of the present application is simple, has low requirements for equipment, the raw materials are cheap and easy to obtain, the cost is low, the requirements for experimental environment are low, no volatile gas is generated, and it is harmless to human body; 4) The vanadium-tungsten bimetallic oxide film prepared by the present application has high light modulation amplitude and high coloring efficiency. BRIEF DESCRIPTION OF DRAWINGS

[0017] Other features, objects and advantages of the present application will become more apparent through reading the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1SEM photograph of the vanadium tungsten bimetallic oxide thin film prepared in Example 1; Figure 2 XRD pattern of the vanadium tungsten bimetallic oxide thin film prepared in Example 1; Figure 3 Cyclic voltammogram of the vanadium tungsten bimetallic oxide thin film prepared in Example 1; Figure 4 Color change effect diagram of the vanadium tungsten bimetallic oxide thin film prepared in Example 1, wherein (a) is a colored state, and (b) is a faded state; Figure 5 Transmittance curve of the vanadium tungsten bimetallic oxide thin film prepared in Example 1; Figure 6 Response time curve of the vanadium tungsten bimetallic oxide thin film prepared in Example 1; Figure 7 Coloring efficiency curve of the vanadium tungsten bimetallic oxide thin film prepared in Example 1; Figure 8 Constant current charge-discharge curve of the vanadium tungsten bimetallic oxide thin film prepared in Example 1; Figure 9 SEM photograph of the vanadium tungsten bimetallic oxide thin film prepared in Example 2; Figure 10 Color change effect diagram of the vanadium tungsten bimetallic oxide thin film prepared in Example 2, wherein (a) is a colored state, and (b) is a faded state; Figure 11 SEM photograph of the vanadium tungsten bimetallic oxide thin film prepared in Example 3; Figure 12 Color change effect diagram of the vanadium tungsten bimetallic oxide thin film prepared in Example 3, wherein (a) is a colored state, and (b) is a faded state; Figure 13 SEM photograph of the vanadium tungsten bimetallic oxide thin film prepared in Comparative Example 1; Figure 14 Color change effect diagram of the vanadium tungsten bimetallic oxide thin film prepared in Comparative Example 1, wherein (a) is a colored state, and (b) is a faded state; Figure 15 SEM photograph of the vanadium tungsten bimetallic oxide thin film prepared in Comparative Example 2; Figure 16 Color change effect diagram of the vanadium tungsten bimetallic oxide thin film prepared in Comparative Example 2, wherein (a) is a colored state, and (b) is a faded state. DETAILED DESCRIPTION

[0018] The application will be described in detail below with reference to specific embodiments. The following examples will help those skilled in the art to further understand the application, but do not limit the application in any form. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the application. These are all within the scope of protection of the application.

[0019] The amount of inorganic compound added in the following examples can be selected from commercially available products with similar properties. The size of the FTO conductive glass can be adjusted according to the volume of the inner liner of the hydrothermal kettle, and is suitable for other conductive glass substrate materials. Any changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principles of the application are considered equivalent replacement methods and are included within the scope of protection of the application.

[0020] Example 1 First, 0.3510 g of NH4VO3 was weighed into a beaker and added to 40 mL of ultrapure water, heated to 70°C and stirred to dissolve until a transparent yellow solution was obtained. Then, 0.7564 g of C2H2O4·2H2O was added to the above solution according to a molar ratio of NH4VO3 to C2H2O4·2H2O of 1:2, heated and stirred until the solution turned blue. Finally, 0.1530 g of (NH4)2Ce(NO3)6 was added to the above blue solution, and the solution was stirred at room temperature for 10 min to obtain a hydrothermal precursor solution. The obtained solution was transferred to a polytetrafluoroethylene reaction kettle liner, and a clean FTO conductive glass with a size of 2.5×5 cm 10 H2(W2O7)6 was added, and the solution was stirred at room temperature for 10 min to obtain a hydrothermal precursor solution. The obtained solution was transferred to a polytetrafluoroethylene reaction kettle liner, and a clean FTO conductive glass with a size of 2.5×5 cm 2 was placed in the reaction kettle, and the reaction kettle was sealed and placed in a constant temperature drying oven for reaction at 150°C for 2h, and then naturally cooled to room temperature.

[0021] The FTO conductive glass in the reaction kettle was removed, washed with deionized water and anhydrous ethanol, and then naturally dried to obtain a vanadium-tungsten bimetallic oxide film on the FTO conductive glass.

[0022] As shown in Figure 1 , it is an SEM photograph of the vanadium-tungsten bimetallic oxide film prepared in this embodiment. As can be seen from the figure, the film is composed of nanometer hexagonal star-shaped vanadium-tungsten bimetallic oxide, which is assembled from a central polyhedral prism and six peripheral branches. The size of the branch unit gradually decreases from the bottom of the central polyhedral prism to the top, forming a multi-level ladder-like hierarchical structure. This gradient stacking method creates a unique pyramid-like three-dimensional architecture, which has excellent structural stability and can improve the electrochemical cycle stability of the film.

[0023] As shown in Figure 2The XRD spectrum of the vanadium tungsten bimetallic oxide thin film prepared in this example is shown in the figure. As shown in the figure, the diffraction peaks at 14.5°, 24.9°, 27.2°, 37.3°, 50.7° and 56.8° are highly consistent with the standard diffraction data (JCPDF 24-1397) of vanadium tungsten oxide V2WO7; the characteristic peaks observed at 23.8°, 28.8° and 48.4° are typical diffraction peaks of WO θ 2.90 The vanadium tungsten bimetallic oxide thin film prepared in this example is composed of two phases.

[0024] The vanadium tungsten bimetallic oxide thin film obtained in this example was tested in a 0.5 mol·L -1 ZnSO4electrolyte solution using a three-electrode system, in which the prepared thin film was the working electrode, a platinum sheet was the counter electrode, and an Ag / AgCl electrode was the reference electrode. Figure 3 is a cyclic voltammetry (CV) curve at a scanning rate of 5 mV·s -1 The color change can be clearly seen during the test. The thin film gradually turned dark blue when scanned to-1.1 V at a scanning rate of 5 mV·s -1 , and gradually turned yellow-brown when reversely scanned to 0.8 V. The obvious redox peaks in the figure are caused by the charge storage kinetics of the vanadium tungsten bimetallic oxide, which is related to the pseudo-capacitance behavior (Faradaic redox reaction), which is related to the insertion and extraction of Zn 2+ .

[0025] Figure 4 are digital photos of the colored state and the faded state of the thin film, in which (a) is the colored state and (b) is the faded state. The colored state is blue, and the faded state is yellow-brown.

[0026] The electrochemical workstation was connected with a UV spectrophotometer to test the transmittance curves of the colored state and the faded state of the thin film in the wavelength range of 400-1250 nm, and the results are shown in Figure 5 The light modulation amplitude at 1200 nm was 33.6%.

[0027] The electrochromic response time curve of the thin film was further tested at 1200 nm, and the test results are shown in Figure 6 The time required to reach 90% of the light modulation amplitude change value is the response time. It is calculated that the coloring time of the vanadium tungsten bimetallic oxide thin film obtained in this example is about 20.8 s, and the fading time is about 31.2 s.

[0028] Figure 7 ​The current density versus light density curve of the vanadium tungsten bimetallic oxide thin film obtained in this example at 1200 nm was calculated to obtain a coloring efficiency of 60.1 cm 2 / C.

[0029] Figure 8 The constant current charge-discharge curve of the vanadium tungsten bimetallic oxide thin film obtained in this example at a current density of 0.2 mA·cm -2 The area capacity was calculated to be 73.2 mAh·m -2 .

[0030] Example 2 First, 0.2106 g of NH4VO3 was weighed into a beaker and added to 40 mL of ultrapure water, and heated to 80°C and stirred until dissolved to a transparent yellow solution. Then, 0.2269 g of C2H2O4·2H2O was added to the above solution according to a molar ratio of NH4VO3 to C2H2O4·2H2O of 1:1, and heated and stirred until the solution turned blue. Finally, 0.1530 g of (NH4) 10 H2(W2O7)6 was added to the above blue solution, and stirred at room temperature for 10 min to obtain a hydrothermal precursor solution. The obtained solution was transferred to a polytetrafluoroethylene (PTFE) reactor liner, and a clean FTO conductive glass with a size of 2.5×5 cm 2 was placed in the reactor, and the reactor was placed in a constant temperature drying oven and reacted at 150°C for 4 h, and then naturally cooled to room temperature.

[0031] The FTO conductive glass in the reactor was removed, washed with deionized water and anhydrous ethanol, and then naturally dried to obtain a vanadium tungsten bimetallic oxide thin film on the FTO conductive glass. The vanadium tungsten bimetallic oxide thin film obtained in this example was subjected to the same micro-morphology and performance tests as in Example 1. Compared with Example 1, the hydrothermal reaction time was increased by 2 h, resulting in a larger nano-hexagonal star structure of the vanadium tungsten bimetallic oxide thin film prepared in this example (as shown in Figure 9 ), and thus the thickness of the obtained thin film was increased. Therefore, the colors of the colored state and the bleached state were both deeper than those of Example 1 (as shown in Figure 10 ), and the corresponding transmittances were also reduced, while the difference between the two, i.e., the light modulation amplitude, was not much different from that of Example 1, as shown in Table 1.

[0032] Example 3 First, 0.4679 g of NH4VO3 was weighed into a beaker and added to 40 mL of ultrapure water, heated to 90 °C and stirred until dissolved to a clear yellow solution. Next, 0.2536 g of C2H2O4·2H2O was added to the above solution in a molar ratio of NH4VO3 to C2H2O4·2H2O of 2:1, heated and stirred until the solution turned blue. Finally, 0.1457 g of (NH4)2Ce(NO3)6 was added to the above blue solution, heated and stirred until the solution turned yellow. The resulting solution was transferred to a Teflon reaction kettle liner, and a piece of clean FTO conductive glass with a size of 2.5 x 5 cm was placed in the reaction kettle, with the conductive surface facing down. The reaction kettle was sealed and placed in a constant temperature drying oven, and reacted at 180 °C for 1 h, and then naturally cooled to room temperature. 10 H2(W2O7)6, stirred at room temperature for 10 min to obtain a hydrothermal precursor solution. The resulting solution was transferred to a Teflon reaction kettle liner, and a piece of clean FTO conductive glass with a size of 2.5 x 5 cm 2 was placed in the reaction kettle, with the conductive surface facing down. The reaction kettle was sealed and placed in a constant temperature drying oven, and reacted at 180 °C for 1 h, and then naturally cooled to room temperature.

[0033] The FTO conductive glass in the reaction kettle was removed, rinsed with deionized water and anhydrous ethanol, and then naturally air-dried to obtain a vanadium-tungsten bimetallic oxide film with the performance to be tested on the FTO conductive glass. The vanadium-tungsten bimetallic oxide film prepared in this example was subjected to the same microscopic morphology and performance tests as in Example 1. Due to the increase in the molar ratio of vanadium to tungsten and the increase in the reaction temperature, the nanometer hexagonal star structure of the vanadium-tungsten bimetallic oxide film prepared in this example was larger than that of Example 1 (as shown in Figure 11 ), and was more dense. Therefore, the color in the colored state and the faded state was deeper than that of Examples 1 and 2 (as shown in Figure 12 ), and the corresponding transmittance was also reduced, and the difference between the two, i.e. the light modulation amplitude, was not much different from that of Examples 1 and 2, as shown in Table 1.

[0034] Comparative Example 1 In this comparative example, the molar concentration of ammonium metavanadate in the hydrothermal precursor solution was adjusted to 0.015 mol / L.

[0035] First, 0.0702 g of NH4VO3 was weighed into a beaker and added to 40 mL of ultrapure water, heated to 70 °C and stirred until dissolved to a clear yellow solution. Next, 0.1513 g of C2H2O4·2H2O was added to the above solution in a molar ratio of NH4VO3 to C2H2O4·2H2O of 1:2, heated and stirred until the solution turned blue. Finally, 0.0306 g of (NH4)2Ce(NO3)6 was added to the above blue solution, heated and stirred until the solution turned yellow. The resulting solution was transferred to a Teflon reaction kettle liner, and a piece of clean FTO conductive glass with a size of 2.5 x 5 cm 10 H2(W2O7)6, stirred at room temperature for 10 min to obtain a hydrothermal precursor solution. The resulting solution was transferred to a Teflon reaction kettle liner, and a piece of clean FTO conductive glass with a size of 2.5 x 5 cm 2FTO conductive glass, and the FTO conductive glass was placed in a thermostat drying oven after the reaction kettle was sealed, and reacted at 150 ℃ for 2 h, and then naturally cooled to room temperature.

[0036] The FTO conductive glass in the reaction kettle was taken out, washed with deionized water and anhydrous ethanol, and then naturally dried, thereby obtaining a vanadium-tungsten bimetallic oxide film with the performance to be tested on the FTO conductive glass. Compared with Example 1, the concentration of ammonium metavanadate was reduced to 1 / 5, which led to a significant decrease in the size of the hexagonal stars of the prepared vanadium-tungsten bimetallic oxide film, and the distribution was sparse (as shown in FIG. 2B), so that the film was thinner and uneven, which resulted in the color in the colored and faded states being lighter and uneven (as shown in FIG. 2C), and the light modulation amplitude was significantly reduced (as shown in Table 1). Figure 13 Figure 14 The FTO conductive glass in the reaction kettle was taken out, washed with deionized water and anhydrous ethanol, and then naturally dried, thereby obtaining a vanadium-tungsten bimetallic oxide film with the performance to be tested on the FTO conductive glass. Compared with Example 1, the concentration of ammonium metavanadate was reduced to 1 / 5, which led to a significant decrease in the size of the hexagonal stars of the prepared vanadium-tungsten bimetallic oxide film, and the distribution was sparse (as shown in FIG. 2B), so that the film was thinner and uneven, which resulted in the color in the colored and faded states being lighter and uneven (as shown in FIG. 2C), and the light modulation amplitude was significantly reduced (as shown in Table 1).

[0037] Comparative Example 2 In this comparative example, the molar ratio of vanadium to tungsten in the hydrothermal precursor solution was adjusted to 1:1.

[0038] First, 0.3510 g of NH4VO3 was weighed into a beaker, 40 mL of ultrapure water was added, and the solution was heated to 70 ℃ and stirred until it became a transparent yellow solution. Then, 0.7564 g of C2H2O4·2H2O was added to the above solution according to a molar ratio of NH4VO3 to C2H2O4·2H2O of 1:2, and heated and stirred until the solution turned blue. Finally, 0.7651 g of (NH4)2WO4 was added to the above blue solution, and the solution was stirred at room temperature for 10 min to obtain a hydrothermal precursor solution. 10 H2(W2O7)6, and stirred at room temperature for 10 min to obtain a hydrothermal precursor solution. The obtained solution was transferred into a polytetrafluoroethylene inner liner of a reaction kettle, and a piece of clean FTO conductive glass with a size of 2.5×5 cm 2 The FTO conductive glass in the reaction kettle was taken out, washed with deionized water and anhydrous ethanol, and then naturally dried, thereby obtaining a vanadium-tungsten bimetallic oxide film with the performance to be tested on the FTO conductive glass. Compared with Example 1, the concentration of ammonium metavanadate was reduced to 1 / 5, which led to a significant decrease in the size of the hexagonal stars of the prepared vanadium-tungsten bimetallic oxide film, and the distribution was sparse (as shown in FIG. 2B), so that the film was thinner and uneven, which resulted in the color in the colored and faded states being lighter and uneven (as shown in FIG. 2C), and the light modulation amplitude was significantly reduced (as shown in Table 1).

[0039] The FTO conductive glass in the reaction kettle was taken out, washed with deionized water and anhydrous ethanol, and then naturally dried, thereby obtaining a vanadium-tungsten bimetallic oxide film with the performance to be tested on the FTO conductive glass. Compared with Example 1, the concentration of ammonium metavanadate was reduced to 1 / 5, which led to a significant decrease in the size of the hexagonal stars of the prepared vanadium-tungsten bimetallic oxide film, and the distribution was sparse (as shown in FIG. 2B), so that the film was thinner and uneven, which resulted in the color in the colored and faded states being lighter and uneven (as shown in FIG. 2C), and the light modulation amplitude was significantly reduced (as shown in Table 1). Figure 15 The FTO conductive glass in the reaction kettle was taken out, washed with deionized water and anhydrous ethanol, and then naturally dried, thereby obtaining a vanadium-tungsten bimetallic oxide film with the performance to be tested on the FTO conductive glass. Compared with Example 1, the concentration of ammonium metavanadate was reduced to 1 / 5, which led to a significant decrease in the size of the hexagonal stars of the prepared vanadium-tungsten bimetallic oxide film, and the distribution was sparse (as shown in FIG. 2B), so that the film was thinner and uneven, which resulted in the color in the colored and faded states being lighter and uneven (as shown in FIG. 2C), and the light modulation amplitude was significantly reduced (as shown in Table 1). Figure 16 The FTO conductive glass in the reaction kettle was taken out, washed with deionized water and anhydrous ethanol, and then naturally dried, thereby obtaining a vanadium-tungsten bimetallic oxide film with the performance to be tested on the FTO conductive glass. Compared with Example 1, the concentration of ammonium metavanadate was reduced to 1 / 5, which led to a significant decrease in the size of the hexagonal stars of the prepared vanadium-tungsten bimetallic oxide film, and the distribution was sparse (as shown in FIG. 2B), so that the film was thinner and uneven, which resulted in the color in the colored and faded states being lighter and uneven (as shown in FIG. 2C), and the light modulation amplitude was significantly reduced (as shown in Table 1). ​

[0040] Comparative Example 3 In this comparative example, vanadium source is vanadyl sulfate, and tungsten source is sodium tungstate dihydrate.

[0041] First, 0.4891 g of VOSO4 was weighed into a beaker and added to 40 mL of ultrapure water, heated to 70 °C and stirred to dissolve. Next, 0.7564 g of C2H2O4·2H2O was added to the above solution in a molar ratio of 1:2 of VOSO4 to C2H2O4·2H2O, heated and stirred to obtain a blue solution. Finally, 0.1979 g of Na2WO4·2H2O was added to the above blue solution, and stirred at room temperature for 10 min to obtain a hydrothermal precursor solution. The obtained solution was transferred to a polytetrafluoroethylene reaction kettle liner, and a clean FTO conductive glass with a size of 2.5 x 5 cm 2 was placed in the reaction kettle, and the reaction kettle was sealed and placed in a constant temperature drying box for reaction at 150 °C for 2 h, and then naturally cooled to room temperature.

[0042] The FTO conductive glass in the reaction kettle was taken out, washed with deionized water and anhydrous ethanol, and naturally dried. It was found that no thin film was formed on the surface of the FTO conductive glass, and the solution in the reaction kettle liner was still blue. The possible reason is that the vanadium in NH4VO3 used in Example 1 is +5 valence, while the vanadium in VOSO4 in Comparative Example 3 is +4 valence. Therefore, it can be seen that the reaction in the reaction kettle changes under the same conditions after changing the vanadium source and tungsten source, and the vanadium-tungsten double metal oxide thin film cannot be obtained.

[0043] Table 1 Comparison of electrochromic properties of vanadium-tungsten double metal oxide thin films prepared in various examples and comparative examples

[0044] The above describes specific embodiments of the present application. It should be understood that the present application is not limited to the above specific embodiments, and those skilled in the art can make various modifications or modifications within the scope of the claims, which does not affect the essential content of the present application.

Claims

1. A method for preparing a vanadium-tungsten bimetallic oxide electrochromic thin film, characterized in that, Includes the following steps: S1. Dissolve ammonium paratungstate hydrate, ammonium metavanadate and oxalate dihydrate in deionized water and stir to obtain a hydrothermal reaction precursor solution. S2. A hydrothermal reaction is carried out on conductive glass to obtain the product; In step S1, the concentration of ammonium metavanadate in the hydrothermal reaction precursor solution is 0.045~0.1 mol / L; In step S1, the molar ratio of vanadium to tungsten in the hydrothermal reaction precursor solution is 3:1 to 7:

1. In step S1, the molar ratio of ammonium metavanadate to oxalate dihydrate in the hydrothermal reaction precursor solution is 1:2 to 2:

1.

2. The preparation method according to claim 1, characterized in that, In step S1, the stirring is heating stirring, and the heating stirring temperature is 70~90 ℃.

3. The preparation method according to claim 1, characterized in that, In step S2, the temperature of the hydrothermal reaction is 150~180 ℃; the time of the hydrothermal reaction is 1~4 h.

4. The preparation method according to claim 1, characterized in that, In step S2, the conductive glass is selected from any one of FTO conductive glass, ITO conductive glass, and AZO conductive glass.

5. The preparation method according to claim 1, characterized in that, Step S2 specifically includes the following steps: S21. Transfer the hydrothermal reaction precursor solution obtained in step S1 to a hydrothermal reactor, and place a piece of conductive glass obliquely into the hydrothermal reactor with its conductive surface facing down, and seal the hydrothermal reactor. S22. Place the sealed hydrothermal reactor into a constant temperature drying oven to carry out the hydrothermal reaction. After the reaction is completed, allow it to cool naturally to room temperature. S23. Remove the conductive glass from the hydrothermal reactor, clean and dry it to obtain vanadium-tungsten bimetallic oxide.

6. A vanadium-tungsten bimetallic oxide electrochromic thin film, characterized in that, It is prepared by the preparation method described in any one of claims 1-5.

7. An electrochromic device, characterized in that, Including the vanadium-tungsten bimetallic oxide electrochromic thin film as described in claim 6.

Citation Information

Patent Citations

  • Preparation method for tungsten trioxide nanowire electrochromic film

    CN107216045A

  • Preparation method of tungsten oxide / ammonium molybdate composite film for electrochromism

    CN113003944A

  • Preparation method of silicon carbide catalytic membrane with multi-layer structure

    CN114515587A

  • Preparation method of core-shell vanadium pentoxide-tungsten trioxide-molybdenum trioxide nano flower-shaped electrochromic film

    CN114911106A

  • Tungsten-niobium bimetal oxide electrochromic film, electrochromic film electrode and preparation method of tungsten-niobium bimetal oxide electrochromic film electrode

    CN116125716A